Directly coated membrane electrode assemblies for proton exchange membrane water electrolysis - Holzapfel, Peter; Bühler, Melanie; Van Pham, Chuyen; Hegge, Friedemann; Böhm, Thomas; McLaughlin, David; Breitwieser, Matthias; Thiele, Simon (Electrochemistry Communications, 2020)
We present a novel membrane electrode assembly (MEA) fabrication method for proton exchange membrane water electrolysis (PEMWE). Inspired by previous work on PEM fuel cells (PEMFCs), we fabricated PEMWE-MEAs via direct membrane deposition (DMD). DMD-MEAs were fabricated by spray coating the membrane directly onto the cathode electrode – in this case, a carbon cloth substrate with microporous layer coated with Pt/C. The complete DMD-MEAs consisted of the membrane-cathode compound assembled with an anode electrode, which is a porous titanium fiber substrate coated with IrO2. Polarization experiments of DMD-MEAs show promising results: In comparison to a reference catalyst coated membrane (CCM) and a porous transport electrode (PTE) type MEA using a freestanding Nafion 117 membrane, we found very good electrochemical performances for DMD-MEAs. DMD-MEAs show slightly higher activation losses than the reference CCM. However, DMD-MEAs seem to exhibit reduced ohmic and mass transport losses compared to those manufactured using the CCM approach. Compared to the PTE-type reference DMD shows improvements for all three loss mechanisms. Similar as for PEMFCs, DMD may allow for a simplified fabrication route and higher degree of design freedom in PEMWE-MEA manufacturing due to the simple layer by layer fabrication approach.
CRIS-Team Scopus Importer:2019-12-27
Keywords: Direct membrane deposition; PEM water electrolysis; Porous transport electrodes